Research Progress of Photothermal Superhydrophobic Surfaces for Anti-Icing/Deicing - Hui Gao; Tianjun Yin; Jieyin Ma; Yuqin Zhou; Ke Li; Jiayi Bao (Molecules)
Photothermal superhydrophobic surfaces with micro/nano-structured morphologies have emerged as promising candidates for anti-icing and deicing applications due to their exceptional water repellency and efficient solar-to-thermal conversion. These surfaces synergistically integrate the passive icephobicity of superhydrophobic coatings with the active heating capability of photothermal materials, offering energy-efficient and environmentally friendly solutions for sectors such as aviation, wind energy, and transportation. Hence, they have received widespread attention in recent years. This review provides a comprehensive overview of recent advances in photothermal superhydrophobic coatings, focusing on their anti-icing/deicing mechanisms, surface wettability, and photothermal conversion performance for anti-icing/deicing applications. Special emphasis is placed on material categories, including metals and their compounds, carbon-based materials, and polymers, analyzing their structural features and application effectiveness. Furthermore, the application of anti-icing/deicing in various fields is described. Finally, perspectives on future development are presented, including pursuing fluorine-free, cost-effective, and multifunctional coatings to meet the growing demand for innovative, sustainable anti-icing/deicing technologies.